Meneroka selera Langkawi: Crab Farm Langkawi & Mee Udang Ketam Tg Pandan destinasi hidangan laut segar dan keunikan rasa - Abd Aziz, Khairul Naim; Tajam, Jamil; Kamaruddin, Sharir Aizat; Zainol, Zamzila Erdawati; Ahmad, Aziani; Ramli, Rohayu; Nazri, Rosnani; Idris, Nor Shafikah; Roslani, Muhammad Akmal; Badaruzaman, Nor Hashimah (Universiti Teknologi MARA, Kedah, 2025)
The Acedemy of Language Studies, Universiti Teknologi MARA (UiTM) Cawangan Kedah, is excited to present the special issue of its e-magazine, The Epitome – Visit Kedah 2025. This special publication, produced in conjuntion with Visit Kedah 2025, represents our steady dedication to cultivating creativity in language and literature while hinghlighting Kedah’s unique blend of culture, nature, and innovation through diverse written expressions. The primary objective of the Epitome – Visit Kedah 2025, especially as our branch is located in the harth of the state. This special edition invites writers to share their Kedah-inspired stories and experiences through personal essays and short stories, whit the aim of embracing diverse linguistic expressions. Contributions are presented in two languages: English and Bahasa Melayu.